Exposure to polycyclic aromatic hydrocarbons and bone mineral density in children and adolescents: results from the 2011–2016 National Health and Nutrition Examination Survey - Zhang, Peng; Li, Shuailei; Zeng, Hao; Sun, Yongqiang (Frontiers in Public Health, 2025)
IntroductionIdentifying factors that hinder bone development in children and adolescents is crucial for preventing osteoporosis. Exposure to polycyclic aromatic hydrocarbons (PAHs) has been linked to reduced bone mineral density (BMD), although available data, especially in children and adolescents, are limited. We examined the associations between urinary hydroxylated-PAHs (OH-PAHs) and lumbar spine BMD, pelvic BMD, and total BMD among 8–19 years participants (N = 1,332) of the 2011–2016 National Health and Nutrition Examination Survey.MethodsWeighted linear regressions were employed to assess the associations between urinary OH-PAHs and BMD. Additionally, Bayesian kernel machine regression (BKMR) and quantile g-computation (Qgcomp) models were utilized to investigate the effect of co-exposure of PAHs on BMD.ResultsSeveral urinary OH-PAHs exhibited negative associations with lumbar spine BMD, pelvic BMD, and total BMD in children and adolescents. For instance, an increase of one unit in the natural log-transformed levels of urinary 1-hydroxypyrene and 2&3-Hydroxyphenanthrene was linked with a decrease of −0.014 g/cm2 (95% CI: −0.026, −0.002) and −0.018 g/cm2 (95% CI: −0.032, −0.004) in lumbar spine BMD, a decrease of −0.021 g/cm2 (95% CI: −0.039, −0.003) and −0.017 g/cm2 (95% CI: −0.033, −0.001) in pelvic BMD, and a decrease of −0.013 g/cm2 (95% CI: −0.023, −0.002) and −0.016 g/cm2 (95% CI: −0.026, −0.006) in total BMD. The body mass index modified the associations between urinary OH-PAHs and BMD, revealing negative effects on BMD primarily significant in overweight/obese individuals but not significant in underweight/normal individuals. Both the BKMR model and the Qgcomp model indicated a significant negative correlation between the overall effects of seven urinary OH-PAHs and lumbar spine BMD, pelvic BMD, and total BMD.ConclusionOur findings revealed that exposure to PAHs might hinder bone development in children and adolescents, potentially impacting peak bone mass—an essential factor influencing lifelong skeletal health.